The unique properties of microorganisms that form a biofilm of the oral cavity - Loban, H. A.; Faustova, M. O.; Ananieva, M. M.; Basarab, Ya. O. (Zaporozhye Medical Journal, 2019)
The purpose of our work was to highlight contemporary ideas about the features of the oral microbiome existence as a biofilm on its surfaces, to summarize the results of modern studies on the composition, formation and properties of microorganisms that form biofilm by reviewing the scientific literature. A majority of the oral bacteria exist in form of specifically organized biofilms rather than bacteria in a planktonic state. The biofilm mode of growth leads to the expression of gene sets which determine the features of metabolism and properties of microorganisms in biofilms. Bacterial biofilm-specific phenotypes are more virulent and highly resistant to antimicrobial agents. Biofilms offer bacteria several environmental and physiological benefits. These advantages lie in the fact that biofilms are a protective physical barrier for nonspecific and specific bacterial protection during infection; they provide resistance to antimicrobial agents. Modern research methods have been used to study biofilms, which greatly have detailed its composition, structure, properties, and mechanisms of interaction between microorganisms in biofilm. Taking into account the difference in the properties of planktonic cultures and collected in a biofilm, saliva can not be an adequate sample for etiological studies. Despite the fact, that the studies of oral biofilms have obtained important scientific results, control of biofilms remains an unresolved problem and should be one of the important directions of modern research. Conclusions. Dental plaque, which is a typical biofilm of the oral cavity, has several stages of formation and its microbial composition varies from the initial streptococcus burden with high content of actinomycetes and other gram-positive bacteria in biofilm. Microflora of a mature dental plaque is varied with the predominance of anaerobic microorganisms.